Pelvic congestion syndrome. Issue 1 (February 2013) - Robertson, Meiri; McCuaig, Ruth
Abstract: Background : The precise aetiology of pelvic congestion syndrome (PCS) remains poorly understood but is believed to be multifactorial having mechanical, hormonal and psychological components. Materials and methods : Minimally invasive techniques of embolisation or sclerotherapy of the ovarian veins has become the mainstay of treatment for PCS. Studies report a technical success rates from 89–100% and clinical success rates of 58–100%. Conclusions : Embolisation and sclerotherapy can be done as a day surgery procedure concurrently with diagnostic venography and given current evidence provide better long term pain relief than medical therapy.